Responsabilidade por infrações tributárias - Paula Junior, Aldo de (2007)
This scientific piece is aimed at identifying and describing the general normative frameworks of the liability for tax violations under the Brazilian Statute Law, particularly: i) the logical and teleological criteria for the characterization thereof; ii) the responsible subjects; iii) its subjective element (will); iv) the exclusion of liability (from the point of view of the violation and sanction); and v) the extinction thereof. Grounded on the texts of the Statute Law and supported by the Deontic Logic and the General Theory of Law, we developed, through an inferring analytical method, the tax violation and tax sanction profile, to analyze, based on the articulation of the elements thereof, the liability for tax violations, understood as the determination of the consequences of the legal sanction-relation to the subject for the practice of an act inconsistent with the normative system. The Deontic Logic and the General Theory of Law categories were essential to approach this theme due to the insufficient and outdated regulation before the abundance of phatic and the valuable situations imposed by the reality. Despite the controversies and the problems the development of the theme encompasses such as, for instance, the punitive or moratorium nature of fines, the objective or subjective character of the tax violations, the succession of the liability for violations and the extent, appropriateness and range of the voluntary revelation of the violation, we sought to point out, based on the bibliography collected and on the Case Law on the matter, arguments that were disputed for each position, to eventually issue, always concerned about the practical applicability, our understanding stated in a judicious and grounded fashion. The main results achieved are related: i) to the qualification of the tax sanctionrelation as a penalty; ii) to the identification of the model of will valuation in the characterization of the tax violation, based on the purpose of the sanction-relation and on the framework of the Brazilian Tax Code, without immediately applying the criteria of the Criminal or the Civil Law; iii) to the identification of the subjects responsible for the tax sanction-relation, and the agents and the liable ones, with an analytical review of the Case Law on the assignment of liability for violations; iv) to the construction of the violating type and the description of their negative elements (illegality exclusion clauses); v) the description of the liability exclusion clauses, namely the voluntary revelation and the amnesty, in a critical analysis of the Case Law on the matter; vi) the identification of the liability extinction clauses, with emphasis on the redemption and on the lapse and statute of limitations